2013
DOI: 10.1136/bmjopen-2012-002222
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality of 1559 young men from four cities in Japan: a cross-sectional population-based study

Abstract: ObjectivesTo provide information of semen quality among normal young Japanese men and indicate the frequency of reduced semen quality.DesignCross-sectional, coordinated studies of Japanese young men included from university areas. The men had to be 18–24 years, and both the man and his mother had to be born in Japan. Background information was obtained from questionnaires. Standardised and quality-controlled semen analyses were performed, reproductive hormones analysed centrally and results adjusted for confou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 36 publications
3
54
2
1
Order By: Relevance
“…A meta-analysis by Carlsen et al [4] suggested that there has been a general decline in sperm concentration and total sperm count over a period of 50 years. In addition, a recent cross-sectional study of men from Danish and Japanese populations showed that the semen analysis results for young men from the general population were lower than for those men identified as being fertile [5][6][7]. However, the reason for this is unclear.…”
Section: Introductionmentioning
confidence: 88%
“…A meta-analysis by Carlsen et al [4] suggested that there has been a general decline in sperm concentration and total sperm count over a period of 50 years. In addition, a recent cross-sectional study of men from Danish and Japanese populations showed that the semen analysis results for young men from the general population were lower than for those men identified as being fertile [5][6][7]. However, the reason for this is unclear.…”
Section: Introductionmentioning
confidence: 88%
“…A few of the subjects in this study have been described in previous reports (Iwamoto et al, 2013a,b;Sato et al, 2014). Briefly, samples in cohort 1 were recruited from university students in three study centers based in the urology departments at university hospitals in Japan (Kawasaki, Kanazawa and Nagasaki), as previously reported (Iwamoto et al, 2013b). In addition, we recruited participants from university students at a study center in Sapporo, as previously reported (Sato et al, 2014).…”
Section: Two Japanese Cohort Samples and Y Chromosome Haplogroupingmentioning
confidence: 99%
“…However, the most common cause of male infertility is due to sperm production abnormalities such as a low sperm count and/or poor sperm quality [2]. Interestingly, in a recent cross-sectional population study Iwamoto et al [3] reported that semen quality of young Japanese people is lower than that of a reference population of fertile men.…”
Section: Introductionmentioning
confidence: 99%